Calculation of embodied mercury emissions from international trade: An empirical study from China - Yao Qu; Xianhua Wu; Yuanjing Xu; Yiting Wang (Sustainable Operations and Computers)
How to use the world input-output table to calculate the embodied mercury emissions from international trade is important for the determination of mercury emission sources and targeted reduction of mercury emissions. This paper first discusses the current situation of mercury emissions and the progress of academic research, and introduces the calculation methods and data sources of the world input-output table. Then, China's embodied mercury emissions caused by international trade are calculated using the 2019 world input-output table from the Carbon Emission Accounts and Datasets which includes detailed data for 134 sectors in 235 countries. The main conclusions are as follows: labor-intensive and energy-intensive industries have high embodied mercury emissions due to foreign final consumption demand, with the combined emissions from metal smelting, energy supply, and agriculture accounting for over 80 % of the total embodied mercury emissions. Moreover, the embodied mercury emissions caused by the final consumption demand of the United States, Japan, Germany, India, and South Korea are large, accounting for approximately 40 % of the total emissions.